All‐Optical Phosphorene Phase Modulator with Enhanced Stability Under Ambient Conditions. Issue 6 (18th April 2018) - Wang, Yunzheng; Zhang, Feng; Tang, Xian; Chen, Xing; Chen, Yunxiang; Huang, Weichun; Liang, Zhiming; Wu, Leiming; Ge, Yanqi; Song, Yufeng; Liu, Jie; Zhang, Du; et al.
Abstract: All‐optical modulators, wherein signal light can be manipulated by another controlling light, have recently emerged as a promising perspective in all‐optical communications, interconnects and signal processing. Herein, by taking advantage of the strong light‐matter interaction and thickness‐dependent direct energy bandgap in few‐layer phosphorene, an all‐fiber all‐optical modulator based on a Mach–Zehnder interferometer comprising few‐layer fluorinated phosphorene‐deposited microfiber has been devised and further demonstrated with phase modulation ability. The phase shift of the signal light, capable of being converted into intensity modulation, could be readily controlled by the photothermal effect in phosphorene. A maximal phase shift of 8π is obtained at a control light of 290 mW, corresponding to a conversion efficiency of 0.029 π mW −1 . The optical information carried by the control light is successfully copied towards the signal light with a modulation depth of 17 dB and a rise time constant of 2.5 ms. Stability under ambient conditions is enhanced significantly thanks to atomistic fluorination in phosphorene that can overcome drawbacks of easy oxidation of intrinsic phosphorene and maintain performance for a long term. This prototypical phosphorene‐based all‐optical phase modulator will have a great potential to be applied in all‐optical information processing and be integrated into optical fiber systems. Abstract : An all‐fiber all‐optical phase modulator is proposed based on few‐layer fluorinated phosphorene with enhanced stability under ambient conditions. Thanks to the large photothermal effect of phosphorene, this prototypical all‐optical phase modulator can be used as all‐optical phase shifter, all‐optical intensity modulator and all‐optical information loader, and may be used in negative logic systems.